Arecoline cannot alter testicular dysfunction and pineal activation caused by noise in wistar rat. (1st January 2018) - Saha, Indraneel; Chatterjee, Aniruddha; Chatterji, Urmi; Maiti, B. R.
Abstract: Millions of people consume betel nut for increased capacity to work and for stress reduction. The nut contains arecoline, which has multiple side effects on endocrine functions. Objective of the work is to investigate pineal–testicular responses to noise and after arecoline treatment in noise in rats. Noise exposure (100 dB, 6 h daily, 10 days) caused pineal stimulation ultrastructurally and at indoleamines level. Leydig cell dysfunction with fall of testosterone level and suppression of sex accessories were noticed. In contrast, pineal activity was inhibited and reproductive functions were stimulated after arecoline administration, confirmed from reversed changes to those of noise. Arecoline treatment in noise exposure showed same results as in noise both in pineal and in reproductive functions. It is concluded that noise causes testicular dysfunction probably by gonadotropin suppression induced by pineal melatonin in noise. Furthermore, arecoline cannot prevent it in noise in rats.